2022
DOI: 10.1002/qua.27063
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking quantum chemistry compound methods for the temperature‐dependent thermochemical data of SixHy and SixFy series

Abstract: Accurate thermochemical data of SixHy and SixFy series is a prerequisite for high‐end materials design. In this study, the standard enthalpies of formation (∆fHnormalθ) of SixHy and SixFy were calculated from atomization and isodesmic reactions using the composite methods CBS‐QB3, G3, G4, W1U, W1BD, and W2‐F12. Second, their temperature‐dependent thermochemical parameters (∆𝑓𝑆θ and Cp) are derived from the optimized geometries and frequency calculation at B3LYP/cc‐pV(T + d)Z level. In addition, this paper us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Zhang et al 43 found that VEGF mediated pain together with immune T cells and B cells, while Duzhong (Eucommiae Cortex) could effectively regulate inflammatory and immune responses and produce analgesic effects on peripheral nerve roots. Guo et al 44 found that the iridoid components contained in Eucommia bark, flowers, and leaves could exert analgesic effects by regulating sodium ions and glutamate receptors. Si et al 45 studied quercetin and sciatic nerve pain in rats and found that quercetin could inhibit the signal pathway Wnt/β-catenin and downstream COX-2 and iNOS targets, and alleviate sciatic nerve pain.…”
Section: Mechanism Of the Effective Components Of Duzhong (Eucommiae ...mentioning
confidence: 99%
“…Zhang et al 43 found that VEGF mediated pain together with immune T cells and B cells, while Duzhong (Eucommiae Cortex) could effectively regulate inflammatory and immune responses and produce analgesic effects on peripheral nerve roots. Guo et al 44 found that the iridoid components contained in Eucommia bark, flowers, and leaves could exert analgesic effects by regulating sodium ions and glutamate receptors. Si et al 45 studied quercetin and sciatic nerve pain in rats and found that quercetin could inhibit the signal pathway Wnt/β-catenin and downstream COX-2 and iNOS targets, and alleviate sciatic nerve pain.…”
Section: Mechanism Of the Effective Components Of Duzhong (Eucommiae ...mentioning
confidence: 99%
“…In fact, while in the case of CF and CF + the situation is relatively benign, there being available thermochemical values for CF that arguably appear reliable, things are veritably more complicated in the case of SiF and SiF + . Namely, the values for the enthalpy of formation of SiF available from the literature 24,25,29,69,71,77–88 encompass a spectacularly wide range, differing on the extremes by more than 16 kcal mol −1 , as demonstrated in Table 3. In principle, one might venture assuming that the values reported from the three most accurate electronic structure approaches 71,81,82 are likely the most reliable.…”
Section: Thermochemical Considerationsmentioning
confidence: 99%
“…In fact, while in the case of CF and CF + the situation is relatively benign, there being available thermochemical values for CF that arguably appear reliable, things are veritably more complicated in the case of SiF and SiF + . Namely, the values for the enthalpy of formation of SiF available from the literature 24,25,29,69,71,[77][78][79][80][81][82][83][84][85][86][87][88] encompass a spectacularly wide range, differing on the extremes by more than 16 kcal mol À1 , Fig. 6 Energies of the lowest vibrational levels of the electronic ground state of SiF + with respect to its v + = 0 level as a function of…”
Section: Thermochemical Considerationsmentioning
confidence: 99%
“…Integrating convolutional and transformer structures in SNNs can help process both local and global information simultaneously, potentially improving the performance of SNNs. In the realm of artificial neural networks (ANNs), a similar idea was adopted in various models (Chen et al, 2022;Guo et al, 2022;Peng et al, 2023).…”
Section: Introductionmentioning
confidence: 99%